Implementasi Aplikasi Happily Interactive Learning untuk Meningkatkan Hasil Belajar IPA Kelas VI Di SDN 02 Ampenan - Maulida, Nurul; Astawa, I Made Sujwasa; Khaer, Fikratul (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
The low science learning outcomes of sixth-grade students at SDN 02 Ampenan on the topics of the skeleton, joints, and muscles, with a mastery level of only 31.58%, indicate the need for more interactive and engaging learning media. This study aimed to improve science learning outcomes through the implementation of the Happily Interactive Learning application, which was specifically designed with various gamification features such as Cheerful Learning Materials, Trio Fun Assessment, Adventure Attendance, and Achievement Gallery. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model with two cycles involving 19 sixth-grade students at SDN 02 Ampenan. Data were collected through observation, learning outcome tests, and student response questionnaires, and were analyzed using descriptive qualitative and quantitative methods. The results showed a significant improvement in learning mastery from 31.58% in the pre-action stage to 78.95% in Cycle 1, reaching 100% in Cycle 2 with a class average of 83.68. The application also successfully enhanced students’ motivation and active participation, with 95% of students reporting that learning became more enjoyable. The implementation of the Happily Interactive Learning application proved effective as an innovative digital learning media capable of transforming science learning into a more interactive, meaningful, and enjoyable experience.